1996
DOI: 10.1111/j.1468-232x.1996.tb00417.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sector‐Specific Skills in Post displacement Earnings

Abstract: This article examines how one form of transferable skills, those valued within an industry or sector, may influence reemployment and earnings following permanent job loss. The empirical analysis finds limited evidence of a sector‐specific component to the returns to job tenure. The importance of these skills varies across sectors, with the strongest evidence found for sectors with sustained labor demand and growing employment. There is stronger evidence, particularly in reemployment, for a broader form of sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 18 publications
2
56
1
Order By: Relevance
“…For manufacturing workers, Jacobson, LaLonde and Sullivan (1993) found that the main determinant of wage loss after six years of displacement is whether he/she gets (or not) a job in the manufacturing sector, but the 4-digit SIC industry where the reemployment takes place is not relevant. Kletzer (1996) provides further arguments and reaches a slightly different conclusion.…”
Section: The Role Of Specific Skills In the Labour Marketmentioning
confidence: 99%
See 4 more Smart Citations
“…For manufacturing workers, Jacobson, LaLonde and Sullivan (1993) found that the main determinant of wage loss after six years of displacement is whether he/she gets (or not) a job in the manufacturing sector, but the 4-digit SIC industry where the reemployment takes place is not relevant. Kletzer (1996) provides further arguments and reaches a slightly different conclusion.…”
Section: The Role Of Specific Skills In the Labour Marketmentioning
confidence: 99%
“…Involuntary mobility and the reward displaced workers receive for accumulated skills have been a source of great interest for labour economists since the late 1980s (for a survey see Fallick, 1996;and Kletzer, 1996).This research programme aims to answer questions such as: how important are specific skills, and how are the earnings of displaced workers affected by these skills? A myriad of papers have approached the issue of transferability of skills by addressing wage changes associated with job mobility.…”
Section: The Role Of Specific Skills In the Labour Marketmentioning
confidence: 99%
See 3 more Smart Citations